2018
DOI: 10.1111/maps.13124
|View full text |Cite
|
Sign up to set email alerts
|

Compositional variability on the surface of 1 Ceres revealed through GRaND measurements of high‐energy gamma rays

Abstract: High-energy gamma rays (HEGRs) from Ceres's surface were measured using Dawn's Gamma Ray and Neutron Detector (GRaND). Models of cosmic-ray-initiated gamma ray production predict that the HEGR flux will inversely vary with single-layer hydrogen concentrations for Ceres-like compositions. The measured data confirm this prediction. The hydrogen-induced variations in HEGR rates were decoupled from the measurements by detrending the HEGR data with Ceres single-layer hydrogen concentrations determined by GRaND neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, the derived elemental abundances of C or Fe from these darkening agents significantly exceed those typically encountered in CCs, of a few wt.% C and ∼20 wt.% Fe (Lodders et al., 1998). The abundances and spatial distributions of H, C, K, Fe, and constraints on average atomic mass were determined from GRaND data throughout Ceres' regolith, to depths of a few decimeters (Lawrence et al., 2018; Prettyman et al., 2017; Prettyman, Yamashita, Ammannito, Castillo‐Rogez, et al., 2018). Though GRaND has spatial resolution much larger than that of VIR (∼400 km vs. ∼1 km, respectively), the informed globally averaged abundances of C (8–14 wt.%) and Fe (15–17 wt.%) are higher than the aforementioned values estimated from VIR data.…”
Section: Introductionmentioning
confidence: 99%
“…However, the derived elemental abundances of C or Fe from these darkening agents significantly exceed those typically encountered in CCs, of a few wt.% C and ∼20 wt.% Fe (Lodders et al., 1998). The abundances and spatial distributions of H, C, K, Fe, and constraints on average atomic mass were determined from GRaND data throughout Ceres' regolith, to depths of a few decimeters (Lawrence et al., 2018; Prettyman et al., 2017; Prettyman, Yamashita, Ammannito, Castillo‐Rogez, et al., 2018). Though GRaND has spatial resolution much larger than that of VIR (∼400 km vs. ∼1 km, respectively), the informed globally averaged abundances of C (8–14 wt.%) and Fe (15–17 wt.%) are higher than the aforementioned values estimated from VIR data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ammonium-bearing minerals are ubiquitous on the surface of Ceres, even though they show a difference in abundance and in chemical form (De Sanctis et al 2016;Ammannito et al 2016). The observed mineralogy requires pervasive and long-standing aqueous alteration (De Sanctis et al 2016;Ammannito et al 2016), as also suggested by the spatial uniformity of element abundance measurements of equatorial regolith (Prettyman et al 2016;Lawrence et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…The global map of hydrogen abundance obtained by GRaND indicates the presence of ice buried below the Cerean regolith, which is increasingly abundant moving away from the equator to high latitudes (Prettyman et al 2016;Lawrence et al 2018). Indeed, local exposure of water ice has been identified on the surface of Ceres, for example, in the craters Oxo and Juling (Combe et al 2016(Combe et al , 2019Raponi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, information contained high‐energy gamma rays by Lawrence et al. () show regional variations in iron abundance. The ice table contains about 10 wt% water ice, most likely of endogenic origin, indicating water left over from the early mineralization process.…”
Section: The Dawn Mission Contributionmentioning
confidence: 99%